Oil dependence is transport running out of affordable fuel?. - Transport Research Centre; International Transport Forum; Organisation for Economic Co-operation and Development; ProQuest (Firm) (Paris : OECD/ITF, 2008)
Oil consumption is increasingly concentrated in transport and relatively limited fluctuations in transport demand can have increasingly significant effects on oil prices. This Round Table assesses the policy instruments available to address oil security and climate change and examines their interaction with measures to manage congestion and mitigate local air pollution. A number of incompatibilities and trade-offs are identified underlining the importance of integrated policy making. The report includes an examination of the factors that drive oil prices in the short and long term and a discussion of the outlook for oil supply.--Publisher's description.
Peak oil and the evolving strategies of oil importing and exporting countries / by Kjell Aleklett -- Future prices and availability of transport fuels / by David L. Greene -- Medium-term oil market uncertainties / by Lawrence Eagles -- Long-run trends in transport demand, fuel price elasticities and implications of the oil outlook for transport policy / by Kenneth A. Small, Kurt Van Dender.
"Transport Research Centre."
At head of title: OECD; International Transport Forum.
Includes bibliographical references.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2018. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Petroleum industry and trade; Petroleum industry and trade -- Government policy; Petroleum reserves -- Economic aspects; Petroleum products -- Prices; Electronic books